PELAKSANAAN DAN PENGAWASAN PENDIDIKAN ISLAM DALAMPEMBINAAN PERILAKU KEAGAMAAN (Studi Kasus di Daerah Rawan Konflik di Lampung Tengah) - rohman, Nur (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
This research was conducted to analyze theimplementation and supervision of Islamic education inone of the conflict prone areas namely Central Lampungof Lampung Province. This research is a qualitativeresearch with a descriptive approach. In this study, fourMadrasah Tsanawiyah in conflict-prone areas in CentralLampung have been used as the research subjects andinformants. Samples were taken by purposive samplingand data were analyzed with qualitative analysis. Theresults of this study found out that there were nosignificant differences from the process of educationimplementation and supervision in conflict-prone areasand low-conflict areas in Central Lampung. The thingthat distinguishes between the two is in terms ofmanaging extracurricular activities which in low-proneareas tend to direct more extracurricular activities in thecultivation of Islam, even making the generalextracurricular become Islamic nuances. In addition, inthe process of supervising Islamic religious education inMadrasah Tsanawiyah, the role of school principals ismore dominant than school supervisors.